QM-MM Investigation of the Reaction of Peroxynitrite with Carbon Dioxide in Water - González Lebrero, Mariano Camilo (2007)
We have investigated the reaction of peroxynitrite with carbon dioxide in aqueoussolution by means of combined quantum-classical (QM-MM) molecular dynamics simulations.In our QM-MM scheme, the reactant was modeled using density functional theory with a Gaussianbasis set, and the solvent was described using the mean-field TIP4P force field. The free energyprofile of this reaction has been computed using umbrella sampling and multiple steeringmolecular dynamics (MSMD) schemes. Umbrella sampling methods turned out to be much moreefficient than MSMD schemes, due to the possibility of employing a combination of classicaland QM-MM thermalization schemes. We found the presence of a significant barrier in the freeenergy profile associated with the reaction in solution, which is not present in vacuum, that maybe ascribed to the significant charge redistribution upon reaction and the concomitant solvationpattern changes.